The C-Type Lectin Receptor Dectin-2 Is a Receptor for Aspergillus fumigatus Galactomannan - Jennifer L. Reedy; Arianne J. Crossen; Paige E. Negoro; Hannah Brown; Rebecca Ward; Diego A. Vargas-Blanco; Kyle D. Timmer; Christopher M. Reardon; Kyle J. Basham; Michael K. Mansour; Marcel Wüthrich; Thierry Fontaine; et al. (2023)
Aspergillus fumigatus is a ubiquitous environmental mold that causes significant mortality particularly among immunocompromised patients. The detection of the Aspergillus-derived carbohydrate galactomannan in patient serum and bronchoalveolar lavage fluid is the major biomarker used to detect A. fumigatus infection in clinical medicine. Despite the clinical relevance of this carbohydrate, we lack a fundamental understanding of how galactomannan is recognized by the immune system and its consequences. Galactomannan is composed of a linear mannan backbone with galactofuranose sidechains and is found both attached to the cell surface of Aspergillus and as a soluble carbohydrate in the extracellular milieu. In this study, we utilized fungal-like particles composed of highly purified Aspergillus galactomannan to identify a C-type lectin host receptor for this fungal carbohydrate. We identified a novel and specific interaction between Aspergillus galactomannan and the C-type lectin receptor Dectin-2. We demonstrate that galactomannan bound to Dectin-2 and induced Dectin-2-dependent signaling, including activation of spleen tyrosine kinase, gene transcription, and tumor necrosis factor alpha (TNF-α) production. Deficiency of Dectin-2 increased immune cell recruitment to the lungs but was dispensable for survival in a mouse model of pulmonary aspergillosis. Our results identify a novel interaction between galactomannan and Dectin-2 and demonstrate that Dectin-2 is a receptor for galactomannan, which leads to a proinflammatory immune response in the lung. IMPORTANCE Aspergillus fumigatus is a fungal pathogen that causes serious and often fatal disease in humans. The surface of Aspergillus is composed of complex sugar molecules. Recognition of these carbohydrates by immune cells by carbohydrate lectin receptors can lead to clearance of the infection or, in some cases, benefit the fungus by dampening the host response. Galactomannan is a carbohydrate that is part of the cell surface of Aspergillus but is also released during infection and is found in patient lungs as well as their bloodstreams. The significance of our research is that we have identified Dectin-2 as a mammalian immune cell receptor that recognizes, binds, and signals in response to galactomannan. These results enhance our understanding of how this carbohydrate interacts with the immune system at the site of infection and will lead to broader understanding of how release of galactomannan by Aspergillus effects the immune response in infected patients.